2020
DOI: 10.1007/s10620-020-06140-6
|View full text |Cite
|
Sign up to set email alerts
|

Teduglutide Promotes Epithelial Tight Junction Pore Function in Murine Short Bowel Syndrome to Alleviate Intestinal Insufficiency

Abstract: Background In short bowel syndrome, epithelial surface loss results in impaired nutrient absorption and may lead to intestinal insufficiency or intestinal failure. Nucleotide oligomerization domain 2 (Nod2) dysfunction predisposes to the development of intestinal failure after intestinal resection and is associated with intestinal barrier defects. Epithelial barrier function is crucial for intestinal absorption and for intestinal adaptation in the short bowel situation. Aims The aim of the study was to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 65 publications
4
25
0
Order By: Relevance
“…Mice develop severe diarrhea and thus high content of stool water after ICR 22 . Previous studies have shown that treatment with the GLP‐2R agonist teduglutide reduced stool water content in the early phase (eg, at day 7) but not in the late phase (eg, at day 14) 24 . To test whether dapiglutide promotes similar effects, stool water content was measured.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice develop severe diarrhea and thus high content of stool water after ICR 22 . Previous studies have shown that treatment with the GLP‐2R agonist teduglutide reduced stool water content in the early phase (eg, at day 7) but not in the late phase (eg, at day 14) 24 . To test whether dapiglutide promotes similar effects, stool water content was measured.…”
Section: Resultsmentioning
confidence: 99%
“…The humane end point included a wellness score below 4 points and weight loss >20%. Stool was collected on postoperative days 2, 7, 10, and 14 and analyzed as described previously 24 . In brief, mice were singly placed into an empty cage covered with tissue paper and observed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP‐1 agonists, which are widely used for the treatment of diabetes mellitus, have recently been proposed to ameliorate muscle wasting by suppressing myostatin and muscle atrophic factors (such as atrogin‐1 and muscle RING‐finger protein‐1 ( MuRF‐1 )), and enhancing myogenic factors including MyoG and MyoD 40 . Pharmacologic GLP‐2‐stimulation promotes gut‐specific growth, enhances intestinal epithelial function and alleviates malnutrition, likely secondary contributes to the gut‐specific pro‐absorptive effects 41 . Similarly, ghrelin has been suggested to exert protective effects on fasting‐induced muscle atrophy in ageing mice through an enhanced expression of myogenic genes and decreased expression of degradation genes 42 .…”
Section: The Gut‐skeletal Muscle Axismentioning
confidence: 99%
“…40 Pharmacologic GLP-2-stimulation promotes gut-specific growth, enhances intestinal epithelial function and alleviates malnutrition, likely secondary contributes to the gut-specific pro-absorptive effects. 41 Similarly, ghrelin has been suggested to exert protective effects on fasting-induced muscle atrophy in ageing mice through an enhanced expression of myogenic genes and decreased expression of degradation genes. 42 The effects of these hormones on muscle wasting associated with chronic gastrointestinal diseases have not been studied yet.…”
Section: The G Ut-s K Ele Tal Muscle a Xismentioning
confidence: 99%